Building Buddhist Human Relationships in Administration - (แสนแป้), พระมหาอานนท์ ชวนาภิภู; สติมั่น, อุทัย (Journal of Educational Review Faculty of Education in MCU, 2018)
Human relationship is essential to every organization because human relationship is required in all work. Human relationship can be science and art to strengthen relations with love, affection, respect, cooperation, loyalty and success. A good relationship is one of main factors which contribute to establish the better collaborative successful work. In Buddhism, the Sangahavatthu Dhamma is the principle in building a good relationship. A good executive should take all measures to create a good relationship for the advantages of organization. The work will go smoothly and efficiently with collaboration of the organization members.